India, The Fourth Industrial Revolution and Government Policy - Patanjali, S.; Subramaniam, D. (Arthshastra Indian Journal of Economics & Research, 2019)
The Fourth Industrial Revolution (also called Industry 4.0) has the potential to bring about changes, which could be called 'revolutionary'. The earlier Industrial Revolutions were in ages when time and technology moved more slowly, especially across boundaries. Now, the time gap for transfer of technologies from one point of the globe to another has dropped. Technology and innovations such as artificial intelligence and 3D printing are spreading more quickly and becoming ubiquitous. The world governments, particularly in the U.S., the European Union, and China, are backing the private sectors where the innovation and investments into latest, ground breaking technologies are taking place. The governments are working to provide an environment to take advantage of the developments as well as to safeguard their economies against potential misuses. The article examined some of the developments related to the Fourth Industrial Revolution in India and across the globe. The article reviewed available literature to understand what some of these benefits could be, and what some of the potential pitfalls are. Given the huge potential impact, the paper sought to examine what the various stakeholders can do to respond and make India better prepared and quicker to adapt to gain the benefits. The article attempted to evaluate whether the government and stakeholders are ready to receive the latest technologies in India and what steps can be taken to create an enabling environment to ensure that the Fourth Industrial Revolution is not another missed opportunity.